Damage-control resuscitation in obstetrics. (16th February 2022) - Carvajal, Javier A.; Ramos, Isabella; Kusanovic, Juan P.; Escobar, María F.
Abstract: Severe obstetric hemorrhage is a catastrophic event and represents the main cause of maternal morbidity and mortality worldwide. The elevated mortality rate due to hemorrhage is associated with metabolic complications and organ hypoperfusion that may trigger a state of irreversible coagulopathy. Thus, the use of conventional measures to control bleeding frequently generates a vicious cycle in which the patient continues bleeding (prolonging surgical times). Damage-control surgery has proven to be feasible and effective in the context of obstetric hemorrhage. It combines surgical and resuscitative measures that generate successful results in the control of refractory bleeding, ultimately decreasing mortality in patients being in critical condition.